Collagen--calcium phosphate composites. - Lawson, A; Czernuszka, J (1998)
There is a widespread clinical need for bone augmentation and replacement. The major solid phases of bone are collagen and calcium phosphate and a bone analogue based on these two constituents should have some useful properties. In this review this theme is developed and the properties of natural and naturally based composites are compared. Composites have been produced by the precipitation of calcium phosphates on to collagen and a summary of the methods and results from mechanical testing and scanning electron microscopy are presented. Composites with mechanical properties intermediate between cancellous and cortical bone have been produced. The review concludes by explaining some of the mechanical properties of the composites, using knowledge of the hierarchical architecture of bone and results from microscopical examination of the fractured composites.